2016
DOI: 10.1080/15548627.2016.1256933
|View full text |Cite
|
Sign up to set email alerts
|

HLH-30/TFEB-mediated autophagy functions in a cell-autonomous manner for epithelium intrinsic cellular defense against bacterial pore-forming toxin inC. elegans

Abstract: Autophagy is an evolutionarily conserved intracellular system that maintains cellular homeostasis by degrading and recycling damaged cellular components. The transcription factor HLH-30/TFEB-mediated autophagy has been reported to regulate tolerance to bacterial infection, but less is known about the bona fide bacterial effector that activates HLH-30 and autophagy. Here, we reveal that bacterial membrane pore-forming toxin (PFT) induces autophagy in an HLH-30-dependent manner in Caenorhabditis elegans. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 59 publications
1
41
0
Order By: Relevance
“…Importantly, in murine macrophages, both TFEB and TFE3 were shown to be activated and translocated to the nucleus upon pathogen infection or stimulation with TLR ligands, where they collaborate in mediating the transcriptional upregulation of several cytokines and chemokines involved in antimicrobial immune response [6, 18, 19]. This functional conservation of the TFEB/TFE3 pathway is further supported by a recent study showing that bacterial membrane pore-forming toxin induces cellular autophagy in an HLH-30-dependent manner in C. elegans [20]. However, the mechanisms by which nematode and mammalian TFEB/TFE3 are activated during infection are still poorly understood.…”
Section: Introductionmentioning
confidence: 86%
“…Importantly, in murine macrophages, both TFEB and TFE3 were shown to be activated and translocated to the nucleus upon pathogen infection or stimulation with TLR ligands, where they collaborate in mediating the transcriptional upregulation of several cytokines and chemokines involved in antimicrobial immune response [6, 18, 19]. This functional conservation of the TFEB/TFE3 pathway is further supported by a recent study showing that bacterial membrane pore-forming toxin induces cellular autophagy in an HLH-30-dependent manner in C. elegans [20]. However, the mechanisms by which nematode and mammalian TFEB/TFE3 are activated during infection are still poorly understood.…”
Section: Introductionmentioning
confidence: 86%
“…A recent report showed that the PFTs Cry5B and Cry21A, produced by the extracellular Gram-positive bacterium Bacillus thuringiensis, induce autophagy in C. elegans via TFEB/HLH-30. 44 Specifically, C. elegans fed with E. coli expressing Cry5B were examined by electron microscopy and by fluorescence microscopy to detect autophagy marker proteins. Cry5B feeding not only increased the abundance of autophagic vesicles but also induced the nuclear translocation of HLH-30::GFP in intestinal cells.…”
Section: Hlh-30/tfeb and Tolerance Of C Elegans To Infectionmentioning
confidence: 99%
“…Interestingly, transcriptomic analysis of the Cry5B-fed C. elegans revealed that HLH-30/TFEB also regulates the transcription of membrane-repair genes (e.g., the small GTPase rab-5). Autophagy genes are required for the repair of membrane pores induced by Cry5B, 44 suggesting an additional function for autophagy in host defense to PFT-producing bacteria. Among the genes induced by Cry5B are a number related to C-type lectins, lysosomes, peroxisomes, and heat shock proteins, which is in agreement with the overall function of TFEB/HLH-30 in regulating expression of cytoprotective and antimicrobial genes in defense against S. aureus infection.…”
Section: Hlh-30/tfeb and Tolerance Of C Elegans To Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports suggested that Rab5 was significantly abolished in the hlh‐30 (ortholog of TFEB in mammals) mutant C. elegans compare with wild‐type strain . In squamous cell carcinomas, TFEB knockdown induces an enlargement of EEA1 labeled endosomes .…”
Section: Discussionmentioning
confidence: 99%